Comparison between endoscope assisted powered and conventional adenoidectomy - Sahni, Dimple; Kaur, Gurleen; Bhagat, Sanjeev; Singh, Parvinder; Verma, Peeyush; Chhabra, Nitin (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Adenoidectomy is one of the commonest operations done on children. It is conventionally performed using the curettage method. This present study was done to compare the results of endoscopic powered adenoidectomy and conventional adenoidectomy. Methods: The present prospective randomized study was conducted among 50 patients between 4-16 years of age requiring adenoidectomy with or without tonsillectomy in department of ENT in Government Medical College and Rajindra Hospital, Patiala. All the 50 patients were divided into two groups (group A and group B) by systematic random sampling. Group A consisted of 25 patients who underwent conventional curettage adenoidectomy and group B consisted of 25 patients who underwent Microdebrider-Assisted Adenoidectomy. Results: In group A and B, mean±SD intraoperative blood loss (in ml) was 20.60±7.96 and 30.60±7.96 respectively. Mean±SD operative time (in minutes) was 28.60±4.71 in group A, while in group B it was 39.60±4.71 with statistically significant difference. Complete adenoid removal was found in 52% of the subjects in group A while it was found in 96% of the subjects in group B with statistically significant difference. In group A, mean±SD recovery time (in hrs) observed was 33.52±10.58 while in group B, recovery time (in hours) observed was 36.22±11.31. Conclusions: Based on the results of this study, it can be concluded that the new method of microdebrider assisted powered adenoidectomy was found to be safer and more useful tool for adenoidectomy than conventional method.